Songpan Garze fold belt: New petrological and geochronological data - Billerot, Audrey; de Sigoyer, Julia; Duchêne, Stéphanie; Vanderhaeghe, Olivier; Pubellier, Manuel (Himalayan Journal of Sciences, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI = 10.3126/hjs.v5i7.1239 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.32